(untitled) (Orfeu, 2025)
This article investigates the interpersonal relationships experienced in the daily lives of Brazilian orchestra musicians and their connections with different forms of subjective perception of success. The research adopts a sequential mixed method, with the application of a questionnaire and semi-structured interviews. The qualitative analysis, based on thematic axes, reveals tensions between cooperation and competition, hierarchy and autonomy, suffering and fulfillment. The participants’ statements show that institutional and relational conditions directly impact the work experience and the meanings attributed to a musical career. The study contributes to the understanding of the orchestral field as a space for symbolic, affective, and political negotiation, in which success is experienced in a plural and relational way.